1996
DOI: 10.2172/414316
|View full text |Cite
|
Sign up to set email alerts
|

WIPP air-intake shaft disturbed-rock zone study

Abstract: The disturbed-rock zone surrounding the air-intake shaft at the Waste Isolation Pilot Plant (WIPP) site was investigated to determine the extent and the permeability of the disturbed-rock zone as a function of radial distance from the 6.1 m diameter shaft., a different elevations within the Salado. Gas-and brine-permeability tests were performed in the bedded halite of the Salado formation at two levels within the airintake shaft. The gas-and brine-permeabiity test results demonstrated that the radial distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…It is well known that undisturbed salt rock has very low permeability. Based on tests conducted at Waste Isolation Pilot Plant (WIPP) site in New Mexico (USA) [42], it was concluded that the permeability of undisturbed salt is less than 10 -21 m 2 [15,40,43]. Another in situ test in the Amelie salt mine owned by Mines de Potasse d'Alsace (MDPA, France) [39], showed the permeability is in the same order of magnitude as the WIPP site.…”
Section: The Fluid Transfer Properties Of Salt Rockmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that undisturbed salt rock has very low permeability. Based on tests conducted at Waste Isolation Pilot Plant (WIPP) site in New Mexico (USA) [42], it was concluded that the permeability of undisturbed salt is less than 10 -21 m 2 [15,40,43]. Another in situ test in the Amelie salt mine owned by Mines de Potasse d'Alsace (MDPA, France) [39], showed the permeability is in the same order of magnitude as the WIPP site.…”
Section: The Fluid Transfer Properties Of Salt Rockmentioning
confidence: 99%
“…Some authors have performed tests about the development of salt permeability variations with the distance from excavation zone. Gas and brine permeability measurements were conducted in the DRZ around the intake well (AIS) of WIPP [42]. The results showed that they decreased as the distance from excavation zone increases and could reach an order of magnitude of 10 -22 -10 -23 m 2 within the radial distance of 3m away from the well wall (see Fig.…”
Section: Permeability Changes With Axial Stress In the Drzmentioning
confidence: 99%
See 1 more Smart Citation
“…Appendix PAR 12 Intrinsic Permeability-Shaft Disturbed Rock Zone: Along with parameters 9 and 1 1, this discusses in situ measurements made on the Air Intake Shaft (Dale and Hurtado, 1998) and in Room D (Knowles and Howard, 1996). Tables PAR-2 Appendix Peer Conceptual Models: Section 3.7 Disturbed Rock Zone.…”
mentioning
confidence: 99%
“…The results of the AIS field testing indicate a log-linear model is an appropriate assumption (Dale and Hurtado, 1996). 'Therefore, such a model was assumed to describe the DRZ permeability as a function of radial distance and was used to calculate an effective DRZ permeability.…”
Section: Lmplementaltion Of Drz Parameters Into the Conceptual Modelmentioning
confidence: 99%